The Influence of Organizational Culture To Organizational Performance Effectiveness In Politeknik Telkom (The Indonesian Journal of Business Administration, 2012)
Considering the importance of organizational culture towards organizational performance, there should be an evaluation and analysis of the indicators or factors affecting Telkom Polytechnic organizational culture in order to improve the performances of the organization in achieving its goals and objectives that have been set. The indicator which is used to measure cultural organization on this research is the organizational culture according to Ellen Martin. It consists of nine dimensions. The indicators used to measure the effectiveness of organizational performance uses a model developed by Kim Cameron. The data processing uses Structure Equation Model (SEM) and a descriptive analysis of the respondents' answers. Hypothesis test showed a significant relationship occurred between organizational culture towards organizational effectiveness in Telkom Polytechnic. Measurement model test states that the external environment indicators, means to Achieve objectives, process management, employee need and objectives, interpersonal relationships, and leadership affects the organizational culture in Telkom Polytechnic significantly. External environment indicator means to achieve objectives, management process and leadership which have a negative perception from the respondents to be fixed instantly towards continuous improvement. Keywords: Organizational Culture, Organizational Performance Effectiveness, Structure Equation Model (SEM)